2016
DOI: 10.3892/br.2016.651
|View full text |Cite
|
Sign up to set email alerts
|

Deep sea water improves exercise and inhibits oxidative stress in a physical fatigue mouse model

Abstract: Abstract. Physical fatigue is extremely common and occurs daily, and is considered to be associated with oxidative stress. The diverse functions of deep sea water (DSW) have recently gained increasing attention. Previous studies have emphasized the anti-fatigue effect of DSW, but the intrinsic mechanism behind the effect remains to be elucidated. In the imprinting control region (ICR) mice model, DSW delayed the exhaustive swimming time. In addition, DSW decreased the area under the blood lactate (BLA) curve, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…A proof-of-concept study has previously reported a substantially faster recovery (shortened from 48 to 4 h) on both leg muscle power (on a force plate) and aerobic fitness (maximal aerobic power on a cycle ergometer) in men stressed by an initial bout of exercise at high temperature (cycling at ~30°C until a 3% weight loss) with DOM supplementation (Hou et al, 2013 ). Similar results have been shown elsewhere, using different sources of mineral water from depths lower than 0.5 km below the earth's surface (Stasiule et al, 2014 ; Fan et al, 2016 ; Keen et al, 2016 ).…”
Section: Introductionsupporting
confidence: 89%
“…A proof-of-concept study has previously reported a substantially faster recovery (shortened from 48 to 4 h) on both leg muscle power (on a force plate) and aerobic fitness (maximal aerobic power on a cycle ergometer) in men stressed by an initial bout of exercise at high temperature (cycling at ~30°C until a 3% weight loss) with DOM supplementation (Hou et al, 2013 ). Similar results have been shown elsewhere, using different sources of mineral water from depths lower than 0.5 km below the earth's surface (Stasiule et al, 2014 ; Fan et al, 2016 ; Keen et al, 2016 ).…”
Section: Introductionsupporting
confidence: 89%
“…We have previously found an accelerated recovery from muscle fatigue in men consuming DOM drink during recovery after a prolonged exercise ( Hou et al, 2013 ). Similar studies using different sources of mineral water collected from depths lower than 0.5 km below the earth’s surface have demonstrated consistent results in improved muscle fatigue against an exercise challenge ( Stasiule et al, 2014 ; Fan et al, 2016 ; Keen et al, 2016 ). The underlying mechanism to explain the significant outcomes on muscle recovery remains unclear.…”
Section: Introductionmentioning
confidence: 53%
“…In order to avoid accumulating fatigue, athletes adopt several dietary and recovery methods that are individually matched. In recent studies, traditional plants [7], green tea [8,9], astaxanthin [10], fucoidan [11] and deep seawater [12] have demonstrated beneficial effects in the suppression of fatigue accumulation. OM-X is a naturally-fermented plant-based probiotic containing herbs, seaweed, fruits and vegetables.…”
mentioning
confidence: 99%